2001
DOI: 10.1176/appi.ajp.158.6.899
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Regional Brain Glucose Metabolism Measured With Positron Emission Tomography After Paroxetine Treatment of Major Depression

Abstract: These results provide further support for a dysfunction in cortical-limbic circuitry in depression, which is at least partly reversed after successful paroxetine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
310
2
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(362 citation statements)
references
References 48 publications
36
310
2
8
Order By: Relevance
“…However, elevating serotonergic function pharmacologically by chronic treatment with SSRIs improved the dysregulated cerebral blood flow and metabolic activity seen in mPFC of depressed subjects (Kennedy et al, 2001), consistent with the observation that SCIT prevented the CUS-induced deficit in ED set shifting in the present study. Thus, there must be some convergence of effect of SSRI and selective NRI treatment in improving mPFC function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, elevating serotonergic function pharmacologically by chronic treatment with SSRIs improved the dysregulated cerebral blood flow and metabolic activity seen in mPFC of depressed subjects (Kennedy et al, 2001), consistent with the observation that SCIT prevented the CUS-induced deficit in ED set shifting in the present study. Thus, there must be some convergence of effect of SSRI and selective NRI treatment in improving mPFC function.…”
Section: Discussionsupporting
confidence: 91%
“…Depressed patients show altered responses on verbal fluency and attentional set-shifting tasks (Austin et al, 2001;Beats et al, 1996;Purcell et al, 1997), as well as diminished motivation and impaired extradimensional set shifting (Miller and Lewis, 1977;Murphy et al, 1999). Consistent with such neuropsychological findings, imaging studies have shown hypoactive function of prefrontal cortex in depression (Rogers et al, 2004;Sheline, 2003), which was improved upon treatment with antidepressant drugs, such as paroxetine (Kennedy et al, 2001;Prasko et al, 2004).…”
Section: Introductionmentioning
confidence: 80%
“…The ACC plays a central role in processing positively valenced emotions [239] and other rewards [240], and in coding value representations of anticipated rewards [241], as shown in studies of sleep deprivation [242-245], psychopharmacological intervention [246-250], cognitive behavioral therapy [251,252] and a combined approach of therapy and psychopharmacological intervention [231]. …”
Section: Reviewmentioning
confidence: 99%
“…Imaging studies have shown associations between cognitive dysfunction and altered activity in prefrontal cortex in depression (Rogers et al 2004;Sheline 2003). Successful treatment with cognitive behavioral therapy, or antidepressant drugs such as paroxetine, produced concomitant changes in prefrontal cortical function, also revealed in neuroimaging studies (Goldapple et al 2004;Kennedy et al 2001;Prasko et al 2004). …”
Section: Introductionmentioning
confidence: 99%